Desarrollo de un sistema de intercambio de calor para el mejoramiento del proceso productivo en la microempresa Miele&sweet - Calero Jácome, Henry Ramiro (2022)
The main activity of the microenterprise "Miele&Sweet" is the elaboration of products derived from bee honey. This research project focuses on the production of nougat, since it is the most demanded product of the microenterprise. The main problem identified is in the production area, where temperatures are out of range, reaching 27ºC, which the product cannot withstand, causing economic losses and poor quality products. The objective is the proposal of a heat exchange system, being a forced ventilation system for air injection, in order to maintain the right temperature for the product, where the range oscillates between 17ºC and 23ºC, obtaining the product in optimal conditions. The methodologies used are an analytical and deductive study, complying with all the activities for the collection of information, allowing to represent the process by means of flow and process diagrams, for a better understanding. The procedure is the characterization of the thermal conditions within the production area, in order to project a simulation taking into account factors such as external and internal temperature of the microenterprise, as well as relative humidity. On the other hand, the current productivity of the microenterprise is visualized and the result obtained in the simulation is the forced ventilation with two ventilation ducts, reaching a temperature between 20⁰C to 21⁰C with an investment of $1238.82 and its productivity increases by 5% of daily production.